Isolation, characterization, and immunomodulatory activity evaluation of probiotic strains from colostrum and canine milk - Quilodrán-Vega, Sandra Rayén; Muñoz-Flores, Carolina; Pino, Ana; Buldres, Paula; Sandoval, Felipe; Aguirre, Alex; Portillo, Brígida; Parra, Natalie; Altamirano, Claudia; Albarracín, Leonardo; Villena, Julio; Toledo, Jorge R. (Frontiers in Veterinary Science, 2023)
This study aimed to characterize potential probiotic strains for use in dogs to prevent infectious enteropathies. Lactic acid bacteria (LAB) isolated from canine milk and colostrum were characterized according to their functional properties, including their resistance to gastrointestinal conditions, inhibitory effect against pathogens, and intestinal adhesion. The immunomodulatory effects of the strains were also analyzed in in vitro and in vivo studies. Among the strains evaluated, two LAB strains showed remarkable resistance to pH 3.0, bile salts, and pancreatin, as well as inhibitory effects against pathogenic Escherichia coli, Salmonella sp., and Clostridium perfringens. The TUCO-16 and TUCO-17 strains induced a significant increase in the expression of TNF-α, IL-8, and TLR2 in canine macrophages. The oral administration of TUCO-16 and TUCO-17 strains to mice significantly augmented their resistance to pathogenic E. coli or Salmonella intestinal infections. Both canine strains reduced intestinal damage and pathogen counts in the liver and spleen and avoided their dissemination into the bloodstream. These protective effects were related to the ability of TUCO-16 and TUCO-17 strains to differentially modulate the production of IFN-γ, IFN-β, TNF-α, IL-6, KC, MCP-1, and IL-10 in the intestinal mucosa. The results of this work showed that the strains TUCO-16 and TUCO-17 are promising probiotic candidates for improving intestinal health in dogs, particularly in increasing their resistance to Gram-negative pathogens. Further studies are required to effectively demonstrate the beneficial effects of TUCO-16 and TUCO-17 strains in dogs.